The Effect Of Product Quality And Customer Satisfaction On Telkomsel Data Package Customer Retention In Lahat Regency - Putri Maharani Nabila; Melia Andayani; Saparudin Saparudin (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of product quality and customer satisfaction on customer retention among Telkomsel data package users. Based on the results of multiple linear regression analysis, the regression equation obtained is Y = 16.066 + 0.249 X₁ + 0.279 X₂, where the constant value of 16.066 indicates that if the independent variables are ignored, the customer retention value remains at 16.066. The regression coefficient for product quality (X₁) is 0.249, meaning that an increase of one unit in product quality will increase customer retention by 0.249 units. Similarly, the regression coefficient for customer satisfaction (X₂) is 0.279, indicating that an increase of one unit in customer satisfaction will increase customer retention by 0.279 units. The t-test results show that product quality (t = 3.154; Sig = 0.002) and customer satisfaction (t = 2.979; Sig = 0.004) have a significant effect on customer retention, as the significance values are below 0.05. Furthermore, the F-test result shows an F value of 11.850 with a significance of 0.000 < 0.05, indicating that product quality and customer satisfaction simultaneously have a significant influence on customer retention. Therefore, it is essential for the company to continuously improve product quality and pay close attention to customer satisfaction to sustain customer loyalty to Telkomsel's services